Lymphepithelial carcinoma - a rare tumor of the larynx. Case Report - Nogal, Piotr; Staśkiewicz, Michalina; Jackowska, Joanna; Wierzbicka, Małgorzata (Frontiers in Surgery, 2022)
Lymphoepithelioma was described in 1921 separately by Regaud and Schmincke as nests of non-keratinizing squamous cells embedded in a lymphoid stroma (Regaud) and isolated transitional cells scattered in lymphoid tissue resembling sarcoma (Schmincke). Lymphoepithelial tumors are the most common lesions of the nasopharynx, although they have also been reported in other localizations, such as the nasal cavity, maxillary sinus, the base of the tongue, parapharyngeal area, tonsils and thymus. Lymphoepithelioma of the larynx is extremely rare. We present a case of a 55-year-old patient treated due to this type of lesion.